2008
DOI: 10.1080/00016350802192071
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenesis imperfecta – a systematic literature review of associated dental and oro-facial abnormalities and their impact on patients

Abstract: A number of aberrations associated with AI have been reported, but not sufficiently systematic to allow for a secondary analysis and synthesis of the findings. The impact on patients in terms of reduced quality of life and economic burden needs to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 78 publications
3
107
2
8
Order By: Relevance
“…18 Additionally there are other reported skeletal abnormalities such as overbite, overjet and cross bites in this review paper.…”
Section: Characteristics Of Hypomaturationhypoplasia With Taurodontismmentioning
confidence: 99%
“…18 Additionally there are other reported skeletal abnormalities such as overbite, overjet and cross bites in this review paper.…”
Section: Characteristics Of Hypomaturationhypoplasia With Taurodontismmentioning
confidence: 99%
“…Due to the discolouration, sensitivity, and extensive treatment required, the psychosocial impact of AI should not be underestimated. A recent systematic review looking at associated dental and orofacial abnormalities in AI, suggested that further research is required into the quality of life and economic impacts associated with AI 9 . It is surprising that the psychological impact of dental anomalies is a largely unresearched field.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HAI have a low risk for caries 39,48 but often have problems with dental and oral hygiene 10,28 and often present excessive tarter, gingival inflammation and associated periodontal problems 39,45 . The surface roughness of the teeth fosters the buildup of dental plaque and tooth sensitivities make the child feel apprehensive about brushing 28 .…”
Section: Preventionmentioning
confidence: 99%